Evolution of Leadership Communication in European Hotel Chains Since 2000 - Dian Putri Natalina Tampubolon (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
This article explores the evolution of leadership communication within hotel organizations since 2000, focusing primarily on European hotel chains, with comparative insights from other regions. The study synthesizes a wide array of international academic research on leadership, cross-cultural management, and internal communication. It also examines communication practices employed by leading hotel chains such as Accor, IHG, and Hilton. The findings reveal a notable shift in communication styles, from traditional hierarchical, one-way messaging to more participative, dialogic, and emotionally intelligent communication, which is increasingly supported by digital platforms. This shift has been driven by factors such as globalization, workforce internationalization, and the evolving expectations of different generations. The study introduces a conceptual framework that links transformational leadership, cultural intelligence, and digital enablement to enhanced employee engagement and improved service quality. In practice, the paper suggests several key strategies for hotel leaders: investing in systems that prioritize listening, empowering frontline employees to have a voice, providing leadership training in inclusive communication, and implementing mobile-first communication channels that cater to deskless workers. The article concludes that leadership communication is a strategic capability—when leaders communicate with clarity, empathy, and consistency, hotels see improved employee retention, better responsiveness, and higher guest satisfaction.